Amul - 2014 - Dixit, Mukund R. ([London] : SAGE, 2016)
This case describes the challenges faced by Amul in organising the dairy farmers into a co-operative and creating continuous opportunities for value additions. The participants are required to review the developments in the organisation and recommend a future strategy.
Originally Published in: Dixit, M. R. (2014). Amul - 2014. BP0375. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Kaira District Cooperative Milk Producers' Union; Dairy products industry -- Case studies; Cooperative societies -- Management -- Case studies; Corporate governance -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies